Profiling the neuroproteomics of honeybee brain: A clue for understanding the role of neuropeptides in the modulation of aggressivity - Paula, Gabriela Mendonça [UNESP]; da Silva Menegasso, Anally R. [UNESP]; dos-Santos-Pinto, José Roberto Aparecido [UNESP]; Malaspina, Osmar [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier, 2024)
The aggressivity is modulated in honeybee brain through a series of actions in cascade mode, with the participation of the neuropeptides AmAST A (59–76) and AmTRP (254–262). The aggressivity of honeybees was stimulated by injecting both neuropeptides in the hemocoel of the worker honeybees, which were submitted to behavioral assays of aggression. The brain of stinger individuals were removed by dissection and submitted to proteomic analysis; shotgun proteomic approach of honeybee brain revealed that both neuropeptides activate a series of biochemical processes responsible by production of energy, neuronal plasticity and cell protection. In addition to this, AmTRP (254–262) elicited the expression of proteins related to the processing of the potential of action and lipid metabolism; meanwhile AmAST A (59–76) elicited the metabolism of steroids and Juvenile hormone-related metabolism, amongst others. Apparently, the most complex biochemical process seems to be the regulation of ATP production, which occurs at two levels: i) by a subgroup of proteins common to the three experimental groups, which are over−/under-regulated through glycolysis, pyruvate pathway, Krebbs cycle and oxidative phosphorylation; ii) by a subgroup of proteins unique to the each experimental group, which seems to be regulated through Protein-Protein Interactions, where the protein network regulated by AmTRP (254–262) seems to be more complex than the other two experimental groups. Significance: Recently we reported the effect of the neuropeptides AmAST A (59–76) and AmTRP (254–262) in the modulation of the aggressive behavior of the worker honeybees. Up to now it is known that the simple presence of the allatostatin and tachykinin-related-peptide in bee brain, is enough for inducing the aggressive behavior. However, nothing was known about how these neuropeptides perform their action, inducing the aggressive behavior. The results of the present study elucidated some of the metabolic pathways that were activated or inhibited to support the complex defensive behavior, which includes the aggressivity. These results certainly will impact the behavioral research of honeybees, since we are paving the way for understanding the molecular base of regulation, of individual /nest defense of honeybees.
Keywords: Aggressivity; Bee brain; Brain metabolism; Neurohormones; Neuroproteomics